Normative blink reflex data for the EyeStat Device in student athletes. Issue 1 (31st December 2022) - Yengo-Kahn, Aaron M.; Garner, Dena P.; Lessing, Noah; Blough, Jackson; Zuckerman, Scott L.; Gifford, Katherine
Abstract: The blink reflex presents a promising, objective, neurophysiologic measure for use in sports-related concussion diagnosis and monitoring. The purpose of this study was to describe blink reflex metrics obtained using the EyeStat across various demographic factors in a group of healthy high school and collegiate athletes. Participants were 975 healthy high school and collegiate athletes ages 13–23 who underwent pre-season baseline blink reflex testing with EyeStat from 2018 to 2020. Separate two- and three-way analyses of variance tested the effects of age, sex and race on each blink reflex parameter including latency ( ms ), differential latency ( ms ), time under threshold ( ln(ms) ), oscillations (qty), and excursions ( px ). Bivariate correlations demonstrated uniformly negligible (|r|<0.2) inter-measure correlations, except between latency and oscillations (r = −0.37). Latency was significantly slower in males versus females (p = 0.001), while latency in 19–21 year olds (college) was faster as compared to 13–15 year olds (high school) (p = 0.008). Differential latency was faster in females versus males (p = 0.033), and Caucasians had faster differential latency values as compared with African Americans (p < 0.0005). The number of oscillations were significantly higher in females versus males (p < 0.0005), and African Americans demonstrating significantly more oscillations as compared to Caucasians (p = 0.006). Excursions were greater in females compared to males (p = 0.003) and Caucasians demonstrated greater excursions as compared to African Americans (p = 0.008). Natural log of time under threshold resulted in significant differences in race, with Caucasians having lower values compared to African Americans (p = 0.026). The current results provide baseline values when applying this new technology to the assessment and monitoring of concussion.